Toward Health, Safety, Security, & Environment (HSSE) Integration into Business Sustainability of Marine, Shipping, & Logistics Companies in Indonesia - Bakhtiar Nofti Cahyono; Gatot Yudoko (Inclusive Society and Sustainability Studies, 2022)
Awareness to consider HSSE in business operations becomes one of the approaches in sustaining the business of the integrated marine logistics sector. It is because the impact of unmanaged HSSE risk could have significant direct consequences for business in terms of financial & reputation loss. Thus, most companies believe, a proper HSSE management would drive the company's performance and sustain the business. Unfortunately, integrating HSSE into business is not an easy task. There are so many HSSE standards that need to be covered besides other standards that need to be also implemented from many disciplinary aspects. Therefore, the research conducted to identify an HSSE management system that aligns with business sustainability as an integrated management system to provide simplicity, eliminate redundancies, reduce documentation, establish consistency, reduce bureaucracy, cost reduction, streamline processes, optimize resources, consistency objectives across multiple systems, deliver a better result, and gain competitive advantage in supporting to be lean enterprise in driving company to be world-class level. The framework used is ESG by Sustainalytics, which consider three main items, e.g., corporate governance, materiality issues, and idiosyncratic issues. Corporate governance refers to the worldwide standard such as standalone management systems (ISO 14001, ISO 45001, ISM, ISPS, and ANZI Z10) and integrated management systems (PAS 99, ISRS 9, OEMS, and SUPREME). Materiality issues refer to the Sustainalytics and SASB list out. Meanwhile, the idiosyncratic refers to GISIS, IMO data of incidents in the last 5 years. In addition to that, research enriched with a causal effect model in enhancing HSSE excellence. The result of the assessment is a proposed integrated management system categorized into four pillars, i.e., People, Process, Plant, and Performance (4Ps). People consist of Leadership commitment and Training & competency assurance. Process consists of Occupational Health, Safe operation, Security for personnel & asset, Environment management, Hazard & risk management, Compliance, Emergency Management, Contractor & supplier management, Project management, Communication & promotion, and Learning from the event. Plant consists of Reliability & integrity management and Management of change. Performance consists of Result & reviews.